2008
DOI: 10.1021/ja8039629
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Reorganization of Motor-Doped Chiral Liquid Crystals: Bridging Molecular Isomerization and Texture Rotation

Abstract: We recently reported that the photoisomerization of molecular motors used as chiral dopants in a cholesteric liquid crystal film induces a rotational reorganization which can be observed by optical microscopy and produces the motion of microscopic objects placed on top of the film (Feringa, B. L.; et al. Nature 2006, 440, 163; J. Am. Chem. Soc. 2006, 128, 14397). The mechanism underlying the mesoscopic manifestation of the molecular process was not fully understood, and here we present a joint theoretical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 47 publications
3
88
0
Order By: Relevance
“…A variety of these types of compounds have been synthesized and characterized by Feringa et al and other groups [62][63][64][65][66][67][68][69][70][71]. Take compound 17 as an example ( Fig.…”
Section: Handedness Inversion In Overcrowded Alkene-doped Clcsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of these types of compounds have been synthesized and characterized by Feringa et al and other groups [62][63][64][65][66][67][68][69][70][71]. Take compound 17 as an example ( Fig.…”
Section: Handedness Inversion In Overcrowded Alkene-doped Clcsmentioning
confidence: 99%
“…The glass rod rotated in the same direction as the cholesteric texture during the photoisomerization or thermal transition steps. A detailed study was also reported with the investigation of CLC-induced azobenzene dopants and fluorene-based overcrowded alkene dopants [65,68,140]. The authors pointed out that the rotational reorganization resulted from the conversion of the chiral molecular motor dopant to an isomer with a different HTP, leading to a change in the cholesteric pitch.…”
Section: Light-induced Mechanical Motions In Cholesteric Liquid Crystalsmentioning
confidence: 99%
“…The relaxing time required to reach the transparent state was almost constant at room temperature in the absence of UV exposure (Figure 3b). The thermal‐induced reconfiguration is mainly determined by the dark relaxation of helical pitch in the order of hundreds of seconds (Figure S11b, Supporting Information), beyond the characteristic reorganization time of LCs τ = D 2 γ/ K 22 in the order of seconds, where D is the thickness of the cell and γ is the twist viscosity coefficient 76. These results demonstrate that the reversibly dynamic orientation of helical axes can be simply manipulated between homogeneousness and random in accordance with the minimum free energy of CLCs associated with the variation of helical pitch, which is triggered by the stable‐unstable isomerization of chiral motor to external stimuli for many cycles without obvious degradation (Figure S12, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[26,27,43] Convergent to these efforts is the use of photosensitive chiral molecules as molecular switches. While the overall goal of these research areas is somewhat dissimilar, the molecules synthesized by Ferringa and co-workers; [32,44,45] Spada, Gottarelli, and coworkers; [46][47][48] and Li et al [49] offer high HTP materials that allow direct accessibility to the pitch of the CLC helix. Most notably, Spada/Gottarelli and later Li developed axially chiral bis(azo) molecules with an HTP of nearly 60 mm À1 in the trans/trans state.…”
Section: Introductionmentioning
confidence: 99%